2019
DOI: 10.19045/bspab.2019.80014
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal efficiency of native plant extracts against whitefly (Bemasia tabaci) on cotton crop

Abstract: Cotton is one of the major cash crops of Pakistan. A collaborative study was conducted by Sangtani Women Development Organization, Ghazi University Dera Ghazi Khan and Women University Multan under Better Cotton Initiative project to provide an eco-friendly and economical control of white fly, aphid, jassid and thrips. For this purpose, ten locally available leaves of the plant trees were selected and their extracts were made with the help of methanol. White fly population is studied and when it's reached at E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[25] observed that an aqueous extract of M. azedarach has a repent effect against first-instar nymphs of whitefly Trialeurodes vaporariorum. [26] found that the leaf extract of M. azedarach act as an effective insecticide against the adult population of B. tabaci at 4 and 6%. Also, [27] showed that the second nymphal stage of B. tabaci is susceptible to terpenoid extract of M. azedarach.…”
Section: Introductionmentioning
confidence: 99%
“…[25] observed that an aqueous extract of M. azedarach has a repent effect against first-instar nymphs of whitefly Trialeurodes vaporariorum. [26] found that the leaf extract of M. azedarach act as an effective insecticide against the adult population of B. tabaci at 4 and 6%. Also, [27] showed that the second nymphal stage of B. tabaci is susceptible to terpenoid extract of M. azedarach.…”
Section: Introductionmentioning
confidence: 99%